Pengaruh Experience Marketing, Nilai Pelanggan Dan Kepuasan Konsumen Terhadap Loyalitas Pelanggan Go-Jek Di Surakarta - Pamungkas, Caesar Fiero (Universitas Malahayati, 2019)
The research aims to find out and describe the influence of either simultaneously or partialexperiential marketing, customer value, consumer satisfaction on GO-JEK customer loyalty inSurakarta.This research using quantitative descriptive research design. The population is allconsumers who use GO-JEK services in Surakarta infinity people. The number of samples wasdetermined by the formula Hair et al and the results were 100 respondents. The sampling techniqueusing a purposive sampling method. The questionnaire is used for data retrieval. Data analysistechnique used was statistic analysis.The results showed that the experiential marketing F test,customer value, customer satisfaction simultaneously and significantly influenced the GO-JEKcustomer loyalty in Surakarta. The results of the t test show that experiential marketing has a positiveand significant effect on GO-JEK customer loyalty in Surakarta. Customer value does not have apositive and significant effect on GO-JEK customer loyalty in Surakarta. Consumer satisfaction has apositive and significant effect on GO-JEK customer loyalty in Surakarta. The regression model in thisstudy is Y = 9,407 + 0,251X_ (1) + (-0,081X_2) + 0,434X_3 + e. The results of the determination ofthe coefficientindicates experiential marketing, customer value, and consumer satisfaction have aninfluence of 19.4%. towards GO-JEK customer loyalty in SurakartaKeyword: Customer Loyalty, Experiental Marketing, Customer Value, Consumer Satisfation